Il governo del consumo di territorio (2012)
(Good) government of the consumption of the territory is now one of the most difficult challenges facing planning and all the other sciences that contribute to the design of effective urban and territorial policies. With a view to contributing to debate on such issues, the authors reflect on the new forms of public decision-making, on the potential of territorial equalisation and on other sizing mechanisms, with reference both to the areas under transformation and the consolidated urban contexts. Based on an in-depth investigation of regeneration, requalification and densification projects for urban areas or metropolitan regions in Italy, Europe or the rest of the world, the text suggests various strategies for intervention with reference to the Tuscan case.